Steel web panel influence on seismic behavior of proposed precast RCS connections. (August 2021) - Bakhtiari Doost, Rooholah; Khaloo, Alireza
Abstract: In this study, the experimental finding of two half-scale interior prefabricated Reinforced Concrete column to Steel beam (RCS) sub-assemblage with proposed joint formations with and without web panel in the junction is presented. Previous researches about RCS have been performed to study shear strength of steel web panel in the joint by modeling joint component, however rarely have been conducted to evaluate joint shear resistance experimentally. Over the past 30 years, noticeable analytical and experimental assessments have been performed on the cast in place RCS joints, but seldom have been done on the prefabricated RCS. The steel beams in the proposed joint are attached to the expanded steel plates that were mounted on the joint edge. The thickness of beam flanges was increased to amplify the concentrated horizontal force transfer to the panel zone. The samples were subjected to a cyclic lateral load with displacement control. The cracking pattern, hysteresis curves, joint deformation, stiffness changes, and energy absorption were determined. The existence of the steel web panel in the panel zone significantly increases the shear strength of the panel zone and considerably reduces joint deformation. Shear strength enhancement due to existence of steel web panel determined by comparing connections with and without steel web panel in the joint.